A higher protein intake at breakfast and lunch is associated with a higher total daily protein intake in older adults: a post‐hoc cross‐sectional analysis of four randomised controlled trials. Issue 2 (15th November 2020) - Verreijen, A. M.; van den Helder, J.; Streppel, M. T.; Rotteveel, I.; Heman, D.; van Dronkelaar, C.; Memelink, R. G.; Engberink, M. F.; Visser, M.; Tieland, M.; Weijs, P. J. M.
Abstract: Background: A protein intake of 30‐40 g per meal is suggested to maximally stimulate muscle protein synthesis in older adults and could therefore contribute to the prevention of sarcopenia. Protein intake at breakfast and lunch is often low and offers a great opportunity to improve daily protein intake. Protein, however, is known for its satiating effects. Therefore, we explored the association between the amount of protein intake at breakfast and lunch and total daily protein intake in older adults. Methods: Protein intake was assessed by a 3‐day food record in 498 community dwelling older adults (≥55 years) participating different lifestyle interventions. Linear mixed model analysis was used to examine the association between protein intake at breakfast or lunch and total daily protein intake, adjusted for sex, age, body mass index, smoking status, study and total energy intake. Results: After adjustment for potential confounders, a 10 g higher protein intake at breakfast was associated with a 3.2 g higher total daily protein intake ( P  = 0.008) for males and a 4.9 g ( P  < 0.001) higher total daily protein intake for females. A 10 g higher protein intake at lunch was associated with a 3.7 g higher total daily protein intake ( P  < 0.001) for males, and a 5.8 g higher total daily protein intake ( P  < 0.001) for females. Conclusions: A higher protein intake at breakfast and lunch is associated with a higher total daily protein intake in community dwelling older adults. Stimulating a higher protein intake at breakfast and lunch might represent a promising nutritional strategy to optimise the amount of protein per meal without compromising total daily protein intake. Abstract : A higher protein intake at breakfast and lunch is associated with a higher total daily protein intake in community dwelling older adults. This association holds true for animal protein, although not for plant protein for which no association was observed. In all, stimulating a higher protein intake at breakfast and lunch might represent a promising nutritional strategy for optimising the amount of protein per meal without compromising total daily protein intake.